18F-FDG PET/CT revealed primary malignant giant cell tumor of the sacrum: a case report - Feng, Zelong; Yu, Ronghua; Hu, Xianwen (Frontiers in Medicine, 2025)
Primary malignant giant cell tumor of bone (PMGCTB), which is usually confirmed to contain a high-grade sarcomatous component at the time of initial diagnosis, accounts for 1.6% of giant cell tumors of bone (GCTB). PMGCTB usually occurs in the epiphysis of long bones, which is similar to GCTB, and only 1.4–9.4% of GCTB occurs in the spine. PMGCTB in the spine is extremely rare. Herein, we present the case of a 46-year-old man who came to the hospital seeking medical help for lumbosacral pain. Computed tomography (CT) was performed because the clinician suspected that the patient had a herniated disk, and the results showed that the fifth lumbar vertebrae to the second sacral vertebrae showed bone destruction, accompanied by soft tissue tumors near the vertebrae, some of which protruded into the spinal canal and sacral canal. Magnetic resonance imaging (MRI) revealed that the lesion demonstrates an isointense signal on T1-weighted imaging (T1WI), a mixed hyperintense signal on T2-weighted imaging (T2WI), and obvious enhancement on contrast-enhanced T1WI. Fluorine-18 fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/CT imaging showed increased 18F-FDG uptake in the lesion. Subsequently, the patient underwent CT-guided biopsy and was diagnosed with PMGCTB by pathology. Because of the poor prognosis of PMGCTB, early diagnosis is essential for the rational treatment of PMGCTB. In the current study, we will review the relevant literature and discuss the clinical, imaging, pathological characteristics, and differential diagnosis of the relatively rare disease.